2021
DOI: 10.3389/fimmu.2021.692151
|View full text |Cite|
|
Sign up to set email alerts
|

Administration of Multivalent Influenza Virus Recombinant Hemagglutinin Vaccine in Combination-Adjuvant Elicits Broad Reactivity Beyond the Vaccine Components

Abstract: Combining variant antigens into a multivalent vaccine is a traditional approach used to provide broad coverage against antigenically variable pathogens, such as polio, human papilloma and influenza viruses. However, strategies for increasing the breadth of antibody coverage beyond the vaccine are not well understood, but may provide more anticipatory protection. Influenza virus hemagglutinin (HA) is a prototypic variant antigen. Vaccines that induce HA-specific neutralizing antibodies lose efficacy as amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 94 publications
(119 reference statements)
3
28
0
Order By: Relevance
“…The pyrimido-indole TLR4 a is less potent than the conventional MPLA agonist for TLR4, but is more suited for tri-agonist synthesis 25 , 39 . Plasma samples were obtained at days 10, 28, 43 and 103 for probing against an influenza protein microarray described previously 27 , which displayed 125 different monomeric full length HA (HA0) drift variants and 131 HA1 variants, spanning all 18 HA subtypes. Other than transient weight loss in the first 24 h after vaccination, the animals in each group showed normal increases in body weight (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The pyrimido-indole TLR4 a is less potent than the conventional MPLA agonist for TLR4, but is more suited for tri-agonist synthesis 25 , 39 . Plasma samples were obtained at days 10, 28, 43 and 103 for probing against an influenza protein microarray described previously 27 , which displayed 125 different monomeric full length HA (HA0) drift variants and 131 HA1 variants, spanning all 18 HA subtypes. Other than transient weight loss in the first 24 h after vaccination, the animals in each group showed normal increases in body weight (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HA1 fragments contain the variable head domain and part of the more conserved stalk of the protein. Previous studies with this array format have shown that sera with reactivity to the full-length (HA0) may also recognize HA1, depending on whether there are antibodies present against the head 27 , 40 . IgG profiles to HA1 fragments are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a major, highly recommended review article, Irvine and coworkers considered that biotechnology combined with the nanomaterials science could bring about safer and more efficient vaccine formulations with major roles for the nanoparticles (NPs) [ 116 ]. In a fast moving field encompassing cancer nanotechnology [ 50 , 89 , 90 , 95 , 117 ], vaccinology against pathogenic viruses [ 61 , 62 , 96 , 97 , 98 , 99 , 100 , 106 , 118 ], and microbes such as bacteria [ 19 , 108 , 112 , 119 , 120 ], fungi [ 119 ], and parasites [ 22 , 120 , 121 , 122 , 123 , 124 ], elegant nanomaterials that are difficult to scale up for commercialization cannot become useful in clinics [ 116 , 125 ].…”
Section: Nanoparticlesmentioning
confidence: 99%